2010
DOI: 10.1038/nm.2213
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of cardiolipin by the lipid pump Atp8b1 determines the severity of lung injury in experimental pneumonia

Abstract: Pneumonia remains the leading cause of infectious deaths and yet fundamentally new conceptual models underlying its pathogenesis have not emerged. Patients and mice with bacterial pneumonia have marked elevations of cardiolipin in lung fluid, a rare, mitochondrial-specific phospholipid that potently disrupts surfactant function. Intratracheal cardiolipin in mice recapitulates the clinical phenotype of pneumonia including impaired lung mechanics, modulation of cell survival and cytokine networks, and lobar cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
139
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(142 citation statements)
references
References 39 publications
2
139
1
Order By: Relevance
“…1) In Caco-2 cells, depletion of ATP8B1 by RNAi was reported to have no effect on PS translocation (22). 2) Another study proposed that ATP8B1 acts as a cardiolipin importer (23). Therefore, it remains uncertain whether PS is a bona fide substrate for ATP8B1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1) In Caco-2 cells, depletion of ATP8B1 by RNAi was reported to have no effect on PS translocation (22). 2) Another study proposed that ATP8B1 acts as a cardiolipin importer (23). Therefore, it remains uncertain whether PS is a bona fide substrate for ATP8B1.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that exogenous expression of ATP8B1 in the CHO-K1 mutant cell line UPS-1, which is defective in PS translocation, promoted PS translocation from the exoplasmic to the cytoplasmic leaflet (8). In contrast, depletion of ATP8B1 by RNAi had no effect on PS translocation in Caco-2 cells (22), and another study proposed that ATP8B1 acts as a cardiolipin importer (23). Therefore, it remains uncertain whether PS is a bona fide substrate of ATP8B1.…”
mentioning
confidence: 99%
“…CCSP is synthesized and expressed primarily in the larger airway and proximal epithelial cells of the lung (ϳ40% of airway epithelial cells), whereas SPC is synthesized and secreted predominantly by the more distal type II alveolar epithelial cells. To target larger airway-specific expression in adult mice, a 2.3-kb rat CCSP promoter was engineered and has been widely used (127), and, similarly, to target more distal airway-specific expression a 3.7-kb human SPC promoter was generated and has also been widely used (165).…”
Section: Lung Specificitymentioning
confidence: 99%
“…Deficiency of cardiolipin is lethal, resulting in apoptosis, impaired proliferation and reduced energy stores (Kagan et al, 2009;Kirkland et al, 2002;Martens et al, 2014;Sorice et al, 2004). Extracellular cardiolipin levels, such as in lung fluid, are very low, but release of cardiolipin from damaged mitochondria or bacterial membranes into the lung can serve as a damage-associated molecular pattern, causing host cell death under some pathophysiological conditions (Ray et al, 2010). Therefore, tight maintenance of cardiolipin homeostasis is crucial.…”
Section: Introductionmentioning
confidence: 99%